Chapter Quando un 'Tuono' colpisce uno storico: come può nascere un fumetto sulla Resistenza - GALLO, Stefano (Public History of Education. Teorie, esperienze, strumenti, 2022)
The paper deals with the metting and the collective work which led to the publication of the comic book "Bandierine. Tutta una storia di Resistenze". It deas with a group of stories linked to a story which works as a frame. The coordinator of this job was the author and comic book writer Andrea Paggiaro, known also as Tuono Pettinato, who died in june 2021. In order to cope with the history of Resistenza with we took into account the most recent historical literature. Everyone can judge the efficacy of the book after having read it; htis essay tried to describe the pace taken into consideration for publishing the book.